Kajian Teknis Hidrologi dan Hidrogeologi pada Kegiatan Penambangan Nikel di Wilayah IUP PT PS, Kabupaten Kolaka, Sulawesi Tenggara: Hydrogeological and Hydrological Technical Assessment of Nickel Mining Operations at PT PS, Kolaka, Southeast Sulawesi - Farsan, Adwil Rilansyah; Dzakir, La Ode; Amir, Muhamad Karnoha (Journal of Engineering Science and Technology Applications, 2025)
This hydrology and hydrogeology study was conducted to analyze the water resource conditions within the Mining Permit Area (IUP) of PT PS, located in Pomalaa District, Kolaka Regency, Southeast Sulawesi. The study aims to assess rainfall characteristics, runoff discharge, erosion potential, aquifer conditions, and to formulate technical recommendations for mine water management. The data used includes 10-year historical rainfall records, field measurements, geoelectrical surveys, and modeling of discharge and drainage systems. The results show that the site experiences high rainfall with a peak runoff discharge of 96.7 m³/s for a 10-year return period. A shallow aquifer was identified at a depth of 20–30 meters, with an average groundwater level of 20 meters. The recommended infrastructure includes surface drainage channels, sump pits, and settling ponds to manage runoff and mine water efficiently. The study concludes that mining activities in the area are technically feasible, provided that water management systems are implemented in accordance with applicable standards and regulations.